Determinan Belanja Modal Pemerintah Kabupaten/Kota Di Provinsi Sumatera Selatan Periode 2018-2022 - Marserina, Sella; AR, Sopiyan; Nurhasanah, Nurhasanah (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine the effect of regional taxes, regional levies, and other legal income on district/city capital expenditure in South Sumatra Province, which consists of 17 districts/cities in 2023. The sample collection technique used in this research is sampling. fed up. This research uses secondary data with data hypothesis testing tools using Static Product and Service Solutions (SPSS) software version 26, with data analysis methods using multiple linear regression. The results of partial hypothesis testing show that regional tax variables and regional levies have a negative effect on capital expenditure. Furthermore, the results of simultaneous hypothesis testing show that the regional tax variables, regional levies, and other legal income variables together have a negative influence on capital expenditure